Influence of motivational interviewing on postoperative mobilization in the enhanced recovery after surgery (ERAS®) pathway in elective colorectal surgery - a randomized patient-blinded pilot study - Wiesenberger, Rico; Müller, Julian; Kaufmann, Mario; Weiß, Christel; Ghezel-Ahmadi, David; Hardt, Julia; Reißfelder, Christoph; Herrle, Florian (Langenbeck's archives of surgery, 2024)
Early mobilization is an essential component of the Enhanced Recovery after Surgery (ERAS®)-pathway. However, a large percentage of patients fail to achieve the ERAS® recommended goal (360 min out of bed from post-operative day 1/POD1). Motivational Interviewing (MI) is an evidence-based type of patient-centered consultation to promote intrinsic motivation. This study aims to evaluate if MI can improve postoperative mobilization.